Cholesterol Derivatives Based Charged Liposomes for Doxorubicin Delivery: Preparation, In Vitro and In Vivo Characterization - Nie, Yu (Ivyspring International Publisher, 2012)
Cholesterol plays a critical role in liposome composition. It has great impact on the behavior of liposome in vitro and in vivo. In order to verify the possible effects from cholesterol charge, surface shielding and chemical nature, two catalogs of liposomes with charged and PEGylated cholesterols were synthesized. Anionic liposomes (AL) and cationic liposomes (CL) were prepared, with charges from hemisuccinate and lysine in cholesterol derivatives, respectively. Characteristics of different formulated liposomes were investigated after doxorubicin encapsulation, using neutral liposomes (NL) as control. Results showed that after PEGylation, AL and CL liposomes displayed prolonged retention release profile, while kept similar size distribution, encapsulation efficiency, low cytotoxicity and hemolysis comparing with NL. Confocal laser scanning microscopy and flow cytometry experiments confirmed the significantly higher cell uptake from AL and CL vesicles than the NL in mouse breast carcinoma and melanoma cells, human epithelial carcinoma and hepatoma cells. It was in accordance with our corresponding cellular mortality studies of DOX-loaded liposomes. The in vivo anti-tumor effect experiments from charged liposomes also presented much higher tumor inhibition effect (70% vs 45%, p < 0.05) than NL liposomes. This is the first time reporting anti-cancer effect from charged cholesterol liposome with/without PEGylation. It may give deeper understanding on the liposome formulation which is critical for liposome associated drug research and development.